SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN UNTUK KENAIKAN JABATAN DENGAN METODE AHP PADA RESTORAN CARL’S JR: Employee Promotion Selection;Analitycal Hierarchy Process;Decision Support System. - Buani, Duwi Cahya Putri; Alexandre, Michael; Anggraeni Putri, Sukmawati (JURNAL AKADEMIKA, 2021)
Carl's Jr. restaurant is one of the restaurants in Indonesia which is engaged in food and beverages. Carl's Jr. continues to grow by opening branches in various places in Indonesia. Over time, a suitable position is also needed to be placed by someone who is appropriate. The selection of promotions at Carl's Jr. restaurant is still done manually, so it does not cover the possibility if the decision making is only seen from certain aspects. A decision support system is a computerized system for making decisions from structured and semi-structured problems in a company. Analitycal Hierarchy Process (AHP) is a method used for complex decision-making with many criteria. The criteria used as a benchmark in determining the choice of promotion at Carl's Jr. restaurant are: skill evaluation, interview, leadership, action plan, verification or internal audit. After processing the data and analyzing respondents, Ryan Saputra had the highest priority (0.293), Satrio Teguh's second priority (0.237), Ragil Enggal's third priority (0.236), and Dimas Ramadhan's fourth priority (0.234).